HeatMetro: A 3D Code Visualization for Test Debt Analysis in Evolving Systems - Casilla, Braulio Nayap Maldonado; Mogollon, Sergio; Parizaca-Mozo, Paul; Sarmiento-Calisaya, Edgar (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
Traditional test coverage metrics often fail to reveal test debt. Additionally, it is difficult to manually uncover code critical for testing, particularly in complex and rapidly changing components of large systems. However, few tools help developers visually explore test debt. In this work, we introduce HeatMetro, a web-based implementation of the code city metaphor that creates an interactive 3D software visualization and operationalizes a context-aware code coverage criterion for the visual analysis of test debt in large Java and Go projects. The feasibility of HeatMetro is evaluated through a study with developers and projects, which indicates promising results, confirming the tool’s effectiveness in identifying and explaining critical components for testing.